Valorization of Olive Industry Through the Application of Two-Phase Process for Extraction and Improvement of Physical and Chemical Properties of Avocado Oil - Lakrari, K.; Kitane, S.; Hassanain, N.; Alaoui El Belghiti, M. (Asian Journal of Chemistry, 2012)
The objective of this work fits into the framework of sustainable development and environmental protection for a comprehensive management of agribusiness waste, including olive industry in Morocco. Several opportunities for recycling such wastes have the dual benefit of solving the environmental problems and particularly increasing the profitability of olive oil extraction units after the olive season that lasts 100 days only. This gives the possibility of using the same equipment to extract the other varieties of oils i.e., avocado oil, according to the ecological process that we present in this contribution. In this study, we have given, by means of the HPLC analysis, the fatty acid composition of isolated avocado oil and compared the physical and chemical analysis of avocado oil by measuring the electrical resistivity.